The Effectiveness of Android-Based Applications on Mothers’ Knowledge of Toddler Growth and Development: A Literature Review - Fitry Aidina; Helmizar Helmizar; Indrawati Lipoeto (GLOBAL HEALTH SCIENCE GROUP, 2026)
Toddlerhood is a critical period for physical growth and neurodevelopment that determines long-term health outcomes. Inadequate maternal knowledge remains a major barrier to optimal growth and development monitoring, leading to delayed detection of growth and developmental problems. Conventional health education methods often have limited accessibility and sustainability. Therefore, android-based applications have emerged as innovative digital health education tools to support mothers in monitoring toddler growth and development. This study aimed to review the effectiveness of android-based applications in improving mothers’ knowledge of toddler growth and development. A literature review was conducted by analysing five national and international studies published between 2021 and 2024. The selected studies employed quasi-experimental designs involving mothers of toddlers aged 0–59 months. The intervention in all studies was the use of android-based applications related to growth and development education or monitoring, with maternal knowledge as the primary outcome. Data were analysed narratively. All reviewed studies reported statistically significant improvements in mothers’ knowledge following android-based application interventions (p < 0.05). Compared to conventional educational media such as leaflets and face-to-face counselling, android-based applications were more effective in enhancing mothers’ understanding of growth indicators and developmental milestones. Android-based applications are effective educational tools for improving mothers’ knowledge of toddler growth and development and have strong potential to be integrated into maternal and child health programmes.